Citation in Applied Linguistics: Analysis of Introduction Sections of Iranian Master’s These - Jalilifar, Alireza; Dabbi, Razieh (Linguistik Online, 2012)
Writing a master’s thesis, oftentimes the first shot by a novice researcher at writing for academic purposes, requires providing a framework and support by learning how to cite the works of others. Compared to the host of studies on research article introductions as the product of expert writing, little work has been done on citations in master’s thesis introductions (MAIs), and so the paucity of research in this area calls for further investigation into citations in MAIs. To this aim, we compared the use of citation forms in 65 Iranian MAIs in the field of Applied Linguistics. Citation forms were divided into integral which play an overt grammatical role within a sentence and non-integral which play a covert grammatical role in text. Each category was further divided into sub-categories. Analyses of the citation practices indicated that integral citations constituted a greater proportion of citations in the MAIs. The study also examined stance manifested in verb controlling citations and underlined the importance of evidential marking in academic writing and discussed pedagogical implications of the research.